3D shape and texture morphing using 2D projection and reconstruction. (October 2015) - Ludwig, Michael; Berrier, Seth; Tetzlaff, Michael; Meyer, Gary
Abstract: We present an algorithm for morphing shape and view-dependent texture that utilizes an unstructured lumigraph representation to (1) gracefully handle topological changes, (2) create plausible appearance transformations, and (3) provide user control independent from the underlying mesh structure. It works by reducing the otherwise complex problem of a 3D shape and material morph into multiple simpler 2D morphs. The shape morph operates on 2D depth maps and then reconstructs a conventional mesh, making it insensitive to the input geometry quality. Our morphing algorithm robustly handles topology changes and outputs complete meshes and lumigraphs for later use. We show how 2D image morphs can be computed from 3D correspondences, while eliminating ambiguities that might result in the projected 2D morphs. Abstract : Graphical abstract: Abstract : Highlights: We present an algorithm for morphing shape and view-dependent texture. The 3D shape morph is implicit and therefore immune to topological constraints. Complex problem of 3D shape+material morphing is converted to multiple 2D morphs. Morph stages are unstructured lumigraphs with realistic simulation of appearance.